An ultra-high aspect ratio BTO nanowires synthesized via slowing the release of barium ions. (December 2021) - Nie, Lifan; Zhang, Long; Zhou, Quan; Zhang, Zi'ang; Dong, Zhaobo; Liu, Qingyi; Yang, Limei; Zhang, Shaohui; Liu, Zeng; Pan, Gebo
Abstract: Normally, the synthesis of the BaTiO3 nanowires is via the ion exchange of K2 Ti8 O17 nanowires with Ba 2+ under hydrothermal conditions. The concentration of the Ba 2+ should be maintained at a low concentration to slow the ion exchange for preventing the crush of templates, thus reducing the quality and yield of the nanowires. In this paper, insoluble barium salt, that is, barium carbonate (BaCO3 ) powder was used as a Ba 2+ sustained release agent, which can release a sufficient amount of Ba 2+ and keep the low concentration of Ba 2+ for ion exchange. The BaTiO3 nanowires with an ultra-high aspect ratio were prepared by this strategy. Thereafter, XRD, SEM, etc. Were used to characterize the as-obtained samples. Results showed that the obtained nanowires possess an average diameter of 11.6 nm and length up to several microns. Compared with other easily soluble barium salts, BaCO3 can reduce the cation exchange rate and increase the nucleation and growth of BaTiO3 nanowires. Additionally, reliable and reproducible experimental phenomenon showed that the above method has obvious advantages in large-scale production and high consistency, which provides an essential strategy for the application of BaTiO3 nanowires in flexible electronic devices, especially in capacitive sensors, film-type capacitors, and energy-storage devices. Highlights: The synthesized BaTiO3 nanowires are with an ultra-high aspect ratio (>500). Insoluble barium salt was used as a Ba 2+ sustained release agent. This work provides an essential strategy for BaTiO3 nanowires synthesis.